Eksistensi Palinggih Hyang Dewa Di Desa Adat Busungbiu Kecamatan Busungbiu Kabupaten Buleleng - Kadek Yuli Wahyu Astini; Ida Made Windya; I Made Hartaka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Palinggih Hyang Dewa is the belief of the people in the Busungbiu Village which is used as a place to glorify the ancestors who were victims of murder. This palinggih will be built by the family who are the perpetrators. If it is not built and trusted by the perpetrator's family, the perpetrator will experience pain and commotion in the family. Therefore, the existence of the Palinggih is very sacred, so its existence is still maintained today. The formulation of the problem that forms the basis for this research are: (1) What is the structure of Palinggih Hyang Dewa in the Busungbiu Village, Busungbiu District, Buleleng Regency? (2) What is the function of Palinggih Hyang Dewa in the Busungbiu Village, Busungbiu District, Buleleng Regency? (3) What is the philosophical meaning of the existence of Palinggih Hyang Dewa in the Busungbiu Village, Busungbiu District, Buleleng Regency?. These problems were analyzed using several theories, including: (1) Symbol theory to dissect the formulation of the first problem regarding the structure of Palinggih Hyang Dewa, (2) Religious theory to dissect the formulation of the second problem regarding the function of Palinggih Hyang Dewa, (3) Semiotic theory to dissect the formulation of the third problem regarding the philosophical meaning of Palinggih Hyang Dewa. In this study, the following data will be produced: (1) The structural basis of Palinggih Hyang Dewa in the Busungbiu Village which includes: the form, belief in ancestors, and ceremonies used, (2) The function of the existence of Palinggih Hyang Dewa in the Busungbiu Village includes: the religious function, the function of request for tirtha, the function of health and protection, the function of education, and the function of togetherness and harmony, (3) The philosophical meaning of Palinggih Hyang Dewa in the Busungbiu Village includes: the meaning of tattwa, the meaning of holiness, the meaning of beauty, the meaning of ethics, and the meaning of harmony.